Diversity and prevalence of Eimeria species in goats of Nepal - GHIMIRE, TR; ADHIKARI, RB; BHATTARAI, N (Journal of the Hellenic Veterinary Medical Society, 2022)
This study aimed to determine the prevalence of Eimeria and identify its different species in adult goats brought to the Kathmandu valley, Nepal, for commercial meat purposes. Eimeria spp. were present in 916 samples out of 991 examined samples (92.4%). A total of 15 different morphologic forms of Eimeria were detected, with the prevalence rates as follows: E. ninakohlyakimovae (83.0%), E. alijevi (75.2%), E. capralis (75.2%), E. masseyensis (67.2%), E. hirci larger form (63.2%), E. tunisiensis (47.3%), E. charlestoni (33.0%), E. jolchejevi larger form (32.4%), E. arloingi (32.4%), E. caprina (19.3%), E. aspheronica (16.5%), E. jolchejevi smaller form (13.5%), E. christenseni (9.4%), E. hirci smaller form (9.4%), and E. caprovina (8.1%). The current data support the fact that Eimeria species are predominant in adult populations. Therefore, coprologic diagnosis and anticoccidial treatments should be implemented in these populations before their transport to new sites to avoid the transmission.